Application of the RRB Type Cooperative Learning Model (Round Robin Brainstorming) in Improving Student Learning Outcomes in Social Sciences Subjects at SMPN 28 Jakarta - Anggraeni, Noviana; Safitri, Desy; Saipiatuddin, Saipiatuddin (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to find out how successful the implementation of the Round Robin Brainstorming learning model is in improving student learning outcomes and student activity in class during learning activities. This research uses the PTK method or is called classroom action research. The data collection techniques used were observation, teacher and student interviews, learning outcomes tests, post test questions, observation sheets for teacher and student activity. Research findings show that the Round Robin Brainstorming learning model provides an increase in social studies learning outcomes through a cycle stage process. In cycle 1, the results obtained an average value of 70.57, in cycle 2, the results obtained an average value of 78.6, in cycle 3, the results obtained an average value of 83.47, the stages of action taken created significant results and succeeded in achieving IPH ≥ 80% in cycle 3.